Development of a quality control manual for canned mushroom (Agaricus bisporus) - Pang, Betty
This study was made in order to develop a quality control manual from canned French button mushroom (Agaricus bisporus). Objective and subjective tests were conducted to establish levels and tolerances for evaluating the canned product. The objective measurement of the physico-chemical properties of canned mushroom showed a close relation between raw material and finished product quality. Routine cut-out test of the samples stored at 37°C for two weeks indicated a sound product. Sensory evaluation results indicated color, texture, size and flavor of canned mushroom as well as the clarity of the brine to be the critical quality attributes. The established product profile characterized canned mushroom as creamy yellow in color, moderately uniform in size and firm in texture. A quality control manual for canned mushroom was then formed. The manual consists of specifications of minimum and maximum limits for certain quality attributes. However, the goodness of the manual can only be tested through time ans continuous use. Improved test methods, new ideas and subsequent production trials are necessary for some modifications on the manual.